Contested Heritage or Cancel Culture? The Case of Ivan Meštrović’s Public Sculptures in Chicago - Daniela Angelina Jelinčić; James K. Reap (Heritage, 2022)
Social conflicts and political pressures represent a specific man-made hazard for heritage protection and result in contested heritage. One of the recent cases, Equestrian Indians publicly displayed in Chicago, was the subject of contestation following the Black Lives Matter protests. The aim of this paper was to critically assess heritage contestation in this case study, also demonstrating other factors influencing heritage contestation than those so far detected in theory, and to find possible coping strategies. Qualitative mixed methods were applied: desk research, critical instance case study, and unstructured interviews. Analysis was completed in line with four theories (international relations theory, collective memory theory, social movement theory and cancel culture) and the results showed: (a) that the case had no greater effect on international relations of the USA and Croatia; (b) a new type of dissonance: a reversed contestation based on a distorted narrative; (c) illusory resistance in the social movement theory; (d) a new theory termed “cancel heritage”, denoting the cancel culture features a spill-over to a collective memory. Possible coping strategies for heritage protection point to the need for a more nuanced participatory approach while forgetting, but possibly the most effective method leading to a collective psychological liberation is hardly achievable.